Perkembangan Ekonomi dan Keuangan dalam Islam: Inspirasi dari Khulafaur Rasyidin - Ika Khuril A’yuni; EVIE LUTVIA (AL-MUTSLA, 2024)
Islamic economics is the response of Islamic scholars to the economic challenges of their time, which is closely related to the Koran and hadith. Islamic economics is also a social science whose Islamic values ​​influence all of society's economic activities. Islamic economics is part of every aspect of life which is based on four sciences, namely the Al-Quran, Sunnah, Ijma', and Qiyas. This discusses a very inclusive way of life. The aim of this research is to describe the history of public policy and the development of Islamic political economy during the time of Khurafaur Rasyidin. Based on the results of this research, Khulafaur Rasyidin's leadership period consisted of four levels of leadership. The first economic policies implemented during the Khurafaur Rasyidin era were during the Abu Bakr era, the second during the reign of Umar bin Khattab, and the third during the reign of Uthman bin Affan, and finally during the reign of Ali bin Talib. Regarding his leadership, several activities were carried out, namely establishing Baitul, shopping centers, distribution of welfare, pension funds, soldiers' salaries, as well as distribution and collection of zakat to Muslim and non-Muslim communities. All of these activities can help develop the country's economy and improve people's living standards. The method used in this research is the library research method. The data collection technique is to conduct a literature review study regarding the problem to be solved. Keywoards: Public Policy; Islamic Economics; Khulafaur Rasyidin